Natural-resource rents and internal conflicts - Can decentralization lift the curse? - Gunther Markwardt; Mohammad Farzanegan; Christian Leßmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study how natural-resource rents a ffect the risk of internal conflict within countries and how the federal structure of countries influences this relationship. Natural-resource abundance may induce excessive rent-seeking and thus increase the risk of internal conflict. Fiscal and political decentralization as an institutional arrangement for rent-sharing and political codetermination of regions within a country may limit the destructive e ffect of the natural-resource rents on internal stability. Using cross-country and panel data covering the period 19842004 from more than 90 countries, we find evidence that natural-resource rents indeed increase the risk of internal conflict, but this relationship is signi cantly mitigated by decentralization.
Keywords: Q34; H77; P28; 330